Generation of Pearl/Calcium Phosphate Composite Particles and Their Integration into Porous Chitosan Scaffolds for Bone Regeneration - Zhiyi Li; Ihtesham Ur Rehman; Rebecca Shepherd; Timothy E. L. Douglas (Journal of Functional Biomaterials, 2024)
Bone tissue engineering using osteoconductive scaffolds holds promise for regeneration, with pearl powder gaining interest for its bioactive qualities. This study used freeze drying to create chitosan (CS) scaffolds with pearl/calcium phosphate (p/CaP) powders, mimicking bone tissue structurally and compositionally. Characterization included scanning electron microscopy (SEM) and mechanical testing. X-ray diffraction (XRD) Fourier-transform infrared–photoacoustic photo-acoustic sampling (FTIR−PAS), and FTIR- attenuated total reflectance (FTIR-ATR) were used to characterize p/CaP. In vitro tests covered degradation, cell activity, and SEM analysis. The scaffolds showed notable compressive strength and modulus enhancements with increasing p/CaP content. Porosity, ranging from 60% to 90%, decreased significantly at higher pearl/CaP ratios. Optimal cell proliferation and differentiation were observed with scaffolds containing up to 30 wt.% p/CaP, with 30 wt.% pearl powder and 30 wt.% p/CaP yielding the best results. In conclusion, pearl/calcium phosphate chitosan (p/CaP_CS) composite scaffolds emerged as promising biomaterials for bone tissue engineering, combining structural mimicry and favourable biological responses.